SOCIAL ASPECT IN AVENGED SEVENFOLD ‘SO FAR AWAY’ SONG: A CRITICAL DISCOURSE PERSPECTIVE - Izzet Fikrotul Fauqi (JF Publisher, 2022)
Discourse study is an interdisciplinary field that combines linguistics, psychology, poetics, and social sciences, focusing on systematic theory and various contexts. Social cognition is defined as a system of mental structures shared by members of a group, culture, or organization. This research aims to analyze the social aspects of the Avenged Sevenfold song “So Far Away” from a Critical Discourse perspective. It follows a descriptive qualitative design, generating data that describe the ‘who, what, and where of events or experiences’ from a subjective perspective. The analysis begins with an examination of each word in the lyrics, followed by an analysis of the entire song and its social aspects. Based on the results and discussion, it can be concluded that the song reflects Synyster Gates’ feelings after the passing of his best friend, The Rev. Since they had been close friends since childhood, The Rev’s death was deeply painful for Synyster Gates.